Czech SMEs and the Effectiveness of their PPC Advertising - Zachová, Hana (2015)
This thesis examines the problem of evaluating the effectiveness of digital marketing; more specifically it looks at the topic of Pay-per-click advertising on the scope of Small and Medium-sized businesses in the Czech Republic. The thesis provides literature review of the historical and current possible practices of what specific measures can be used to evaluate the success of pay-per-click advertising. Moreover, it connects the measurement subject with the associated area of attribution modeling. This topic represents an important issue for the online marketers mostly because of a currently widely used last-click attribution model that is not able to attribute the fair value of the different channels on the consumer journey to purchase. The primary research conducted in the form of qualitative research through in-depth interviews brings insights into the current practices of selected representatives of Czech SME sector as well as the digital agencies on the matter of measuring the success of online marketing and the attribution modeling. Derived findings give a picture at what stage of development the measurement and attribution of PPC currently is in the Czech SME market.